An Extra‐Broadband VIS‐NIR Emitting Phosphor toward Multifunctional LED Applications. (31st October 2021) - Xiao, Yu; Xiao, Wenge; Wu, Dan; Guan, Linquan; Luo, Min; Sun, Ling‐Dong
Abstract: The development of extra‐broadband emitting phosphors is challenging but meaningful work. So far, however, phosphors that can be effectively excited by GaN‐based blue light‐emitting diode (LED) chips and emit from visible (VIS) to near‐infrared (NIR) regions are still rare. Herein, this study designs an extra‐broadband VIS‐NIR emitting phosphor with emission band ranging from 460 nm to 880 nm (bandwidth > 400 nm) upon 450 nm excitation, owing to an efficient energy transfer from Ce 3+ to the red and NIR emitting Mn 2+ ions in Lu2 BaAl4 SiO12 (LBAS) host. By the analysis of extended X‐ray absorption fine structure (EXAFS) spectra and fluorescence lifetimes, it is demonstrated that the NIR emission most probably originates from those Mn 2+ occupying the dodecahedral sites with high symmetry rather than the exchange‐coupled Mn 2+ ‐Mn 2+ pairs. Furthermore, two single‐phase phosphor‐converted LEDs are fabricated by combining blue LEDs with LBAS:Ce 3+, Mn 2+ phosphors, and thanks to the extra‐broadband emission, the resultant devices may realize multifunctional applications, such as in high‐quality general lighting, NIR spectroscopy, and plant growth lighting. Abstract : The combination of the dual roles of Mn 2+ in generating red and near‐infrared (NIR) emission and the efficient energy transfer from Ce 3+ to Mn 2+ in Lu2 BaAl4 SiO12 garnet leads to an extra‐broadband visible‐NIR emitting phosphor for multifunctional light‐emitting diode (LED) applications. This study demonstrates that Mn 2+ with highly symmetric coordination can efficiently activate broadband NIR phosphors.